Selected Legal Aspects of Transaction Costs - Famulski, Tomasz (Journal of Finance and Financial Law, 2017)
The aim of this article is to identify the relation between transaction costs and the law, both on theoretical and practical grounds. In literature various approaches on the issue of transaction costs are presented, but it was Ronald H. Coase’s discovery and explanation that turned out to be one of the most crucial determinants of the development of Law & Economics. Thereby, the findings of economics on the issue of transaction costs are interfuses L&E as a jurisprudential movement. Detailed analysis of selected current Polish legal regulations lead to a conclusion that some of those regulations generate transaction costs, while other limit the ability to transact. Concurrently, legal regulations that foster reduction of the level of transaction costs are indentified. In general conclusion it can be asserted that the previous assumption – legal regulations can affect transaction costs in both positive and negative way – is true.